2015
DOI: 10.1080/15287394.2014.993779
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Suppressed Prostatic Epithelial Proliferation in a Rat Model of Benign Prostatic Hyperplasia

Abstract: Benign prostatic hyperplasia (BPH), a disease occurring frequently among elderly males, is a slow progressive enlargement of the fibromuscular and epithelial structures of the prostate gland. Dietary factors may influence the prostate and exert an influence on prostatic growth and disease. The current study was undertaken to investigate the protective effect of dietary flaxseed supplementation against testosterone-induced prostatic hyperplasia in male rats. Forty male Wistar rats were divided into 5 groups: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Similar to what has been reported on animal models [52,53], a strong utility of dietary flaxseed lignan extract in improving BPH-related LUTSs, compared to that of alpha1A-adrenoceptor blockers and 5alpha-reductase inhibitors, has been reported by Zhang et al [69]. These authors conducted a randomized clinical trial in which a placebo, 300, or 600 mg/day of secoisolariciresinol diglucoside, a flaxseed extract, were administered to 87 patients affected by BPH and found a decrease in IPSS and improvement of quality of life score and LUTSs, respectively [69].…”
Section: Studies In Humansupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to what has been reported on animal models [52,53], a strong utility of dietary flaxseed lignan extract in improving BPH-related LUTSs, compared to that of alpha1A-adrenoceptor blockers and 5alpha-reductase inhibitors, has been reported by Zhang et al [69]. These authors conducted a randomized clinical trial in which a placebo, 300, or 600 mg/day of secoisolariciresinol diglucoside, a flaxseed extract, were administered to 87 patients affected by BPH and found a decrease in IPSS and improvement of quality of life score and LUTSs, respectively [69].…”
Section: Studies In Humansupporting
confidence: 87%
“…In particular, higher immunohistochemical and Western blot levels of p-ERK1/2 were observed both in rats with BPH plus a high-fat diet and rats with BPH compared to those found in rats with a high-fat diet and in a control group. However, it has also been reported that the administration of flaxseed reduced epithelial cell proliferative activity in rats with BPH [52,53]; this finding led to the supposition that different fat types and contents are involved in BPH onset and maintenance. As further evidence for this hypothesis, Kayode et al emphasized that a ketogenic diet, consisting of high fat, moderate protein and low carbohydrate consumption, ameliorated testosterone propionate-induced BPH in male Wistar rats [54].…”
Section: Studies In Animal Modelsmentioning
confidence: 99%
“…4A, tissues from the BPH group showed swollen prostate and increased supply of blood vessels. However, the major macroscopic parameter of testosterone-treated prostate tissues was ameliorated by 10 mg/kg of 6SL, 40 mg/kg of 6SL and Saw Palmetto (SP), as positive control, commonly recommended as alternative therapeutic of BPH (2830). Factors, including prostate weight, relative prostate weight, and PW/BW ratio, which was increased in the BPH group, were all down-regulated in the SP, 10 mg/kg of 6SL, and 40 mg/kg of 6SL-treated groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although their significant benefit of 5α-reductase inhibitors and natural products (2830), there are several reports raising clinical concerns because of their small effective size and risk of adverse effect including sexual complications (3133). Here, we confirmed that genes related angiogenesis pathways, such as ANPEP , APOLD1 , and VEGFA , were elevated in tissues of BPH patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in 2015, Said et al reported their findings on flax seed supplementation in a BPH-induced cohort of rats. 19 It was found that, in contrast to untreated animals, flax seed administration significantly decreased prostatic vascular endothelial growth factor (VEGF) and prostatic epithelial cell proliferation.…”
Section: Discussionmentioning
confidence: 99%